The real origin of the COVID-19 Pandemic - Trueba, Gabriel (ACI Avances en Ciencias e Ingenierías, 2025)
In December 2019, an outbreak of pneumonia in Wuhan marked the epicenter of the COVID-19 pandemic. Although a novel coronavirus similar to the SARS virus responsible for an epidemic in 2002 was identified, two hypotheses emerged regarding its origin: the live animal market in Wuhan or a potential leak from the Wuhan Institute of Virology (WIV). Most scientific experts support the hypothesis of a natural origin and transmission from the live animal market. However, certain political groups in the United States promoted the lab-leak theory, which undermined trust in scientific communication. One consequence of this mistrust in science was resistance to public health measures such as vaccination, mask-wearing, and social distancing, along with growing skepticism toward scientific activity. These dynamics have serious implications for public health and for future virus surveillance efforts.